Metachronous multicentric giant cell tumor of bone treated with denosumab and mega-prosthesis revision: a rare case report - Lin, Huaitai; Yang, Chanping; Zhu, Jinhao; Yang, Chenyu; Xu, Zijian; Wu, Zejin; Wang, Xinjia; Wang, Weidong (Frontiers in Oncology, 2025)
IntroductionMulticentric giant cell tumor of bone is extremely rare, accounting for less than 1% of all giant cell tumor of bone (GCTB) cases. Metachronous multicentric GCTB is even rarer.Case presentationWe present a rare case of metachronous multicentric giant cell tumor of bone (GCTB) in a 27-year-old male, in whom three distinct lesions developed sequentially over a 10-year period: first in the right distal femur, followed by the proximal femur, and later the proximal tibia. To address progressive disease and prosthetic complications, the patient underwent revision of the mega-prosthesis combined with adjuvant denosumab therapy, followed by curettage of the subsequently emerging tibial lesion.ConclusionThis case illustrates the sequential development of multiple GCTB lesions and the importance of combined surgical reconstruction and denosumab therapy in long-term management.